Bacteriological and Antibiotic Susceptibility Profile of Urinary Tract Infection among Online Motorcycle Drivers in Jakarta, Indonesia - Effendi, Ida; Robertus, Thomas; Samira, Jihan; Devita, Arleen; Kumala, Widyasari; Bella, Isa (Global Medical & Health Communication (GMHC), 2024)
Urinary tract infection (UTI) is a bacterial infection that contributes significantly to morbidity rates. UTI is a health concern due to multidrug-resistant (MDR) organisms. Therefore, the profile of bacteria and antibiotic susceptibility patterns are very important to know in order to make the best treatment choice. Working as an online motorcycle (ojol driver) carries a risk of urinary tract infections. Online drivers are assumed to often hold their urination for short or long periods. The descriptive study with a cross-sectional design was conducted to obtain the prevalence of urinary tract infections, bacteria profile, and antibiotic susceptibility in urine specimens collected from Jakarta ojol drivers in September 2022–Maret 2023. Of 98 midstream urine specimens, 17 samples are considered to have UTI (17.34%). The identification of the 17 isolates shows that the microorganisms' distribution was more likely to be caused by gram-positive than gram-negative bacteria (70.60%). The causative bacteria were coagulase-negative Staphylococcus (17.65%), Escherichia coli (11.76%), and Enterococcus faecalis (11.76%). Our results showed that the prevalence of urinary tract infections in ojol drivers is high with the distribution of the causative organisms by coagulase-negative Staphylococcus, Escherichia coli, and Enterococcus faecalis and still showed good susceptibility to narrow-spectrum antibiotics such as cotrimoxazole.